If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+5(x-4)=2(5x+5
We move all terms to the left:
6+5(x-4)-(2(5x+5)=0
We multiply parentheses
5x-(2(5x+5)+6-20=0
| 5/16y+3/8=21+y | | 5-(n-7)=2(n+5) | | m-2=m/6+8 | | (12x)(12x)=(16+x-2)(16+x-2) | | y2+ 7= 10 | | –2c=–18 | | c–2=-3 | | x(2)-42x=-441 | | 4/5-m+2=6 | | 20=4u-8 | | 3/5x+1/4=7/20-4 | | x–5=3 | | -6(3+7x)=444 | | 16.95+.02x=22.95+.02x | | 4=-2+2s | | 4(g-)=24 | | 13t-7=-48 | | -5+5m=-40 | | 3–r=-10 | | 65(8k+2)=-36 | | 2y=21+4 | | 5a-16=2a+8 | | -5+2k=-39 | | 2(b-6)+4=8 | | 5x+15=7x | | 5(3r-2)=-35 | | -3d/d^2-8+3/d-4=-2/d+2 | | 2x+4=5x+4 | | -8c+11c=-12 | | 5(10x-10)=5(-4+4) | | (2z-3)^(2/5)=(3z)^(1/5) | | Y=50x+8 |